Myozap, a novel intercalated disc protein, activates serum response factor-dependent signaling and is required to maintain cardiac function in vivo - Seeger, Thalia Sandra; Frank, Derk; Rohr, Claudia; Will, Rainer D.; Just, Steffen; Grund, Christine; Lyon, Robert; Luedde, Mark; Koegl, Manfred; Sheikh, Farah; Rottbauer, Wolfgang; Franke, Werner W.; et al. (Circulation research, 2010)
The intercalated disc (ID) is a highly specialized cell-cell contact structure that ensures mechanical and electric coupling of contracting cardiomyocytes. Recently, the ID has been recognized to be a hot spot of cardiac disease, in particular inherited cardiomyopathy. Given its complex structure and function we hypothesized that important molecular constituents of the ID still remain unknown.